Comparative response mechanisms of two cultivars of Musa paradisiaca L. to Fusarium oxysporum f.sp. cubense infection - Duan, Yajie; Jia, Zhiwei; Lu, Zhiwei; Hu, Huigang; Zhan, Rulin (Frontiers in Plant Science, 2025)
With the aim of enhancing plants’ ability to respond to pathogenic fungi, this study focuses on disease resistance genes. We commenced a series of investigations by capitalizing on the pronounced differences in resistance to Fusarium wilt between resistant and susceptible varieties. Through an in-depth exploration of the metabolic pathways that bolster this defense, we identified genes associated with resistance to Fusarium oxysporum f. sp. cubense (Foc). For our analysis, root tissues from seedlings that had been in contact with Fusarium oxysporum for four days were harvested, including both infected and uninfected samples, which served as our study specimens. The crude extract treatment led to a significant increase in malondialdehyde (MDA) levels, lignin content, and phenylalanine ammonia lyase (PAL) activity. Conversely, there was a notable decline in protein content, ergosterol levels, and pectinase activity. In the control group, it was observed that 4,474 genes in the resistant varieties were significantly up-regulated compared to the susceptible varieties. The functional annotation of these differentially expressed genes (DEGs) emphasized their predominant participation in biological processes. Further analysis via the KEGG database revealed that 14 DEGs in the susceptible varieties were particularly enriched in pathways related to plant hormone signaling. Through the perspective of transcriptome data, we focused on genes associated with lignin and cell wall development for Q-PCR validation. Notably, the expression levels of Macma4_02_g07840 (COMT) and Macma4_10_g06530 (CCOAOMT) were relatively elevated. Our findings suggest that the resistance of these varieties to wilt infection can be ascribed to the accumulation of lignin metabolites, which inhibits pathogenic fungus growth by restricting the synthesis of cellular metabolites. The evidence documented in our research provides a framework for a deeper understanding of the disease resistance mechanisms in bananas, laying a solid theoretical foundation for future studies in this area.